P2X4 receptors and neuropathic pain - Tsuda, Makoto; Masuda, Takahiro; Tozaki-Saitoh, Hidetoshi; Inoue, Kazuhide (Frontiers in Cellular Neuroscience, 2013)
Neuropathic pain, a debilitating pain condition, is a common consequence of damage to the nervous system. Neuropathic pain is often resistant to currently available analgesics. A growing body of evidence indicates that spinal microglia react and undergo a series of changes that directly influence the establishment of neuropathic pain states. After nerve injury, P2X4 receptors (P2X4Rs) are upregulated in spinal microglia by several factors at the transcriptional and translational levels. Those include the CC chemokine CCL21 derived from damaged neurons, the extracellular matrix protein fibronectin in the spinal cord, and the transcription factor interferon regulatory factor 8 (IRF8) expressed in microglia. P2X4R expression in microglia is also regulated at the post-translational level by signaling from other cell-surface receptors such as CC chemokine receptor (CCR2). Importantly, inhibiting the function or expression of P2X4Rs and P2X4R-regulating molecules suppresses the aberrant excitability of dorsal horn neurons and neuropathic pain. These findings indicate that P2X4R-positive microglia are a central player in mechanisms for neuropathic pain. Thus, microglial P2X4Rs are a potential target for treating the chronic pain state.